Earthquake in central Italy and velocities structure of the mantle - Tsvetkova, T. A.; Bugaenko, I. V.; Zaets, L. N. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2018)
A three-dimensional P-velocity model of the European mantle built on the Taylor approximation made it possible to analyze the velocity structure of the mantle under the Mediterranean and, in particular, under Central Italy, to a depth of 2500 km.It is shown that the crust earthquakes in Central Italy, characterized by a magnitude up to 7,0, are associated with super-deep fluid processes of the mantle. A possible seismic channel was found, linking the propagation of the fluid process from the lower mantle to the crust inclusive. The manifestations of the super-deep fluid process are isolated at the depths of the lower and middle mantle. In the upper mantle and transition zone of the upper mantle, the channel is determined by the distinguished seismic boundaries of the 2th-generation, which are determined by the transition from the increase of gradients of velocity from depth to descent or vice versa. These seismic boundaries correspond to phase transitions.Consideration of the deep structure of the mantle under Central Italy has shown the presence of low velocities in the area under consideration from the lower mantle to the zone of division-2. The analysis of the structure of tops of the upper mantle showed the presence of the mantle section in area of 13°±0,5 lon.Ч43°±0,5 lat., where the earthquakes with a magnitude up to 7,0 stand out in the crust. A section is timed to the area of thrust Moho boundary of and correlated with its crossing of Ankona-Ancio fault, dissociating the Central Apennines from the North. This region corresponds to a triple intersection of faults and an increased heat flux, and there is also an increased fission of the upper mantle (7 seismic boundaries of the 2th-generation). Depth of occurrence of the main geodynamic boundary is less than 670 km.